Marine Invertebrate Peptides: Antimicrobial Peptides - Wu, Ran; Patocka, Jiri; Nepovimova, Eugenie; Oleksak, Patrik; Valis, Martin; Wu, Wenda; Kuca, Kamil (Frontiers in Microbiology, 2021)
Antimicrobial peptides are the innate immune substances of marine invertebrates forming the first-line of defense used by many organisms against the invading pathogens. As a kind of biological polypeptides with natural immune activities, antimicrobial peptides have a broad spectrum of antibacterial, antiviral and an-ti-tumor activities. Particularly, these peptides have no harm to animals themselves. Compared with tradi-tional antibiotics, antimicrobial peptides have been paid more and more attention because they are not easy to develop drug resistance and have unique mechanism of action. In this paper, marine invertebrates were divided into arthropods, annelids, mollusks, cnidarians and tunicata. Then, we analyzed the types, sources and antimicrobial activities of antimicrobial peptides in each group, respectively. We also reviewed the mechanism of action from three aspects: membrane targeting direct killing effect, non-membrane targeting effect and immune regulation effect. Finally, the application of antimicrobial peptides in practical production and the existing problems were discussed in order to provide some theoretical support for the development of new antibiotics and the wider application.